Nurse and midwife researcher collaboration in eastern sub‐Saharan Africa: a social network analysis - Cato, K.D.; Sun, C.; Dohrn, J.; Ferng, Y.‐h.; Klopper, H.C.; Larson, E. (International nursing review, 2019)
Aim To investigate the collaborative networks among expert clinical nurse and midwifery researchers in eastern and southern Africa. Methods Thirty‐eight clinical nurse and midwifery researchers completed an online survey to analyse collaboration between respondents. Data were analysed using social network analysis, generating a network map and associated measurements. Results Regional collaboration was poor. Those links that did exist centred on geographic proximity and participation in regional and international organizations. Conclusion These results help us to understand better ways to strengthen and support nursing and midwifery clinical research in eastern and southern Africa. Implications for nursing policy Clinical nursing and midwifery research capacity building efforts should focus on supporting collaboration networks among individuals and institutions in the region.